Peran Pemerintah Provinsi Riau dalam Penanganan Konflik Tenurial sebagai Upaya Penyelesaian Kebakaran Hutan dan Lahan di Masa Pandemi - Annisa Dini; Bayu Setiawan; Yusuf Ali; Ganes Harpendya; Fadilah Munawaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Riau is one province of Indonesia known for its forest and land fires. One of the causes of these tragic land fires is tenure conflicts between corporations and indigenous or local peoples. Tenure conflicts became the main reason forest and land fire cases in Riau Province are convoluted. Thus, the resolution takes a long term to resolve. The local government, as a policymaker, has played a pivotal role in resolving tenurial conflicts. This research analyzes local governments' role in handling tenure conflicts in Riau Province by using the structural root causes of conflict, accelerator, trigger (SAT) factor analysis approach and Human Needs Theory. To analyze the role of the Riau Province government in handling tenurial conflict as an effort to resolve forest and land fires during the pandemic, the researcher uses a qualitative approach with a descriptive design presented through data collection from primary and secondary data sources, such as interviews and literature review. This research finds that in handling tenure conflicts, the government of Riau has been facing some challenges in its effort to resolve forest and land fires conflict resolution process.